Eksistensi Sistem Waris Islam Di Tengah Komunitas Muslim: (Studi Kasus Pembagian Harta Waris di Dusun Alastimur Desa Daun Kecamatan Sangkapura Bawean Gresik) - Ainun Barakah; Ulfatun Najiha; Abdul Halim (JURISY: Jurnal Ilmiah Syariah, 2023)
Indonesia as a country with the largest Muslim population in the world is a country whose inheritance distribution system is dualism and pluralism, meaning that, apart from using the Islamic inheritance system, it also applies a customary inheritance system. This is influenced by several factors, including the diversity of tribes, cultures and customs of the population, so that even though the majority of them are Muslim, the customs and cultural heritage of their ancestors are sometimes still strong and upheld. The focus of this research is: 1) How is the system of inheritance distribution in Alastimur hamlet, Daun village 2) What is the existence of the Islamic inheritance system in the midst of the Muslim community. From the results of this study it is known that the practice of inheritance in the Alastimur hamlet uses two inheritance distribution systems, namely the Islamic inheritance system (faraidh) and the customary system. The method used in this study is descriptive qualitative with a phenomenological approach. Collecting data in this study using interviews and documentation techniques. Data analysis was carried out by means of data reduction, data presentation and drawing conclusions. Keywords: Faraidh, customary inheritance system